A study of Saemaul Undong in South Korea: Making self, memory and development - Jeong, Da Un (University of the Witwatersrand, Johannesburg, 2024)
Saemaul Undong (New Village Movement) was South Korea’s state-led rural development project, launched in 1970, under Park Chung Hee’s authoritarian regime. Studies of Saemaul Undong have been deeply polarised, especially along ideological lines, either praising the movement for empowering rural communities, or dismissing it as a tool of political propaganda. While Saemaul Undong has received global attention as a development model in the last two decades, the literature on Saemaul is still limited to judging its success or failure alone. Drawing on a Foucauldian analytic of governmentality and memory-work method, this thesis reveals how Saemaul Undong was not simply imposed by the South Korean state, but also embraced and implemented by rural communities. Taking a triangulated approach of complementing an analysis of state archive materials with participants’ life histories and cultural repertoires of the media, this study explores the experiences, memories and emotions of rural villagers in their engagement with Saemaul Undong and its ‘technologies of the self’. It finds that Saemaul Undong, using visual guidelines and discourses of nation building and ideal citizenship, created a space for the constitution of new types of selves and new ways of relating to the selves, in the long shadow of war, famine and colonialism. This thesis contributes to the fields of development, social movements and state-building in the global South by revealing how power and governance in state-led development projects are played out at the micro level of the self.
Keywords: Saemaul Undong; South Korea; state-led development; authoritarian government; governmentality; subjectivity; memory; life-history; UCTD; SDG-17: Partnerships for the goals